The Influence of ROA and CAR on Stovk Price with Interest Rates As Intervening Variables (Case Study of Bank Rakyat Indonesia Tbk Company) (PERIOD 2010 -2020) - Abi Daud, Muhammad; Suharto; Iwan Kurniawan Subagja (Krisnadwipayana International Journal of Management Studies, 2023)
This research was conducted with the aim of empirically examining the effect of Return on Assets (ROA), and Capital Adequacy Ratio (CAR), partially on stock prices with the intervening variable interest rates in the banking company (Bank Rayat Indonesia Tbk). In addition, this study empirically examines the effect of ROA, CAR, and interest rates simultaneously on the stock price of Bank Rakyat Indonesia Tbk. In this study the authors used quantitative research with an associative approach. Types of secondary data from Quarter I 2010- Quarter IV 2020 data taken from Bank BRI's website on the IDX. Data analysis used classical assumption test, simple linear regression analysis, multiple linear regression analysis, hypothesis testing and path analysis. For the coefficient of determination (R2), where it is found that the greatest direct contribution is the interest rate variable to the stock price of 50.1%, while the indirect contribution is ROA and CAR to stock prices through interest rates of 0.513 or 51.3%.